Lithuanian’s Agriculture and Food Market and European Union - Garuekas, Rimantas; Slatkevičienė, Giedrė (Ekonomika, 2003)
Agriculture is a traditional, very important and diverse field of economy. It is the fourth field according to the proportion of the Gross Domestic Product. In fact, because of some of its features, for example, its seasonal prevalence or its necessity of product. for the existence of the people, agriculture is often considered to he a specific branch of industry which, by all means, needs a specific support of the state. During the integration process into the European Union Lithuania will not be protected from the competition in the agricultural sector. While modernizing the agricultural and food sector, we shall have to pay special attention to the quality of the production, so that it would meet the requirements of the quality of the EU and become competitive. The main aim of Lithuania in the integration process is to increase the quality of the production, its ability to he competitive among the countries of the EU. To achieve these aims there arc all preconditions and prospects: favorable natural conditions, skilled workers, prop natural resources, the experience in the production and traditions, a wide range of scientific study and consultation services.We must give priority to the following agricultural and food industries: dairy products and meat husbandry, gardening and market gardening, flax industry. oil and non-traditional plants, grain, sugar beets. These branches have difficulties in insufficient competition in inner and outer market and also in a small investment ability, and poor technological progress a, well as great production costs. To make the negative consequences of the integration milder, support is given by certain funds, such as PHARE, SAPARD, ISPA, and in the future we will be able to use the means of other funds, too.The industry of milk is acknowledged to be one of the main industries in the development of the agricultural strategy. So after the joining the EU, milk industry branch will receive the greatest attention and financial aid, because its position in the European market will depend on its, competitiveness. After the results, concerning milk industry are assessed, we will be able to state that the Lithuanian milk sector has good prospects, because the quotas agreed upon are quite big (bigger than the previous offer of the European Commission) and the support is also going to be given. Smaller prices than in other countries, the greatest financial support of all the countries candidates and also the direct support promised in 2005 for the milk sold will be the advantages of the milk industry and this will undoubtedly decide good perspectives for the milk sector and it will he competitive in the whole market of the EU.Another sector, foreseen in the priority list in meat sector. To develop this branch of industry there are all preconditions and prospects: favorable natural conditions, qualified workers, sufficient amount of fodder, the experience in animal rearing, meat production and traditions. In addition, the EU has given larger quota. to Lithuania than other countries candidates; larger quotas to beef, mutton, which would intensify the production of this kind of meat. Staving the lack of mutton in the EU, European Commission gave bigger quotas than had been asked. After having evaluating the fact that the rearing of animals ha. decreased because of poor buying capacity, the quotas agreed upon will become a stimulus to develop preat sector. During the integration into the EU and having a wish to be competitive in the meat sector, we should increase the quality of our beef and pork. Out of low quality raw material it is impossible to make good quality meat and its products which would be in great demand and be successfully competitive in the EU and word markets. In the process of integration into the EU and in order to raise the quality of the beet, pork and mutton bought, a new carcass classifying system EUROP has been introduced.Having analysed the indesces of the help to the grain sector and having in mind the situation in the market, it is possible to forecast that the growing of grain will not be competitive. According to the fertility, the cost price of the production and also bearing in mind the buying costs, we will not be able to he competitive in the general market, so will be developing the production for the internal market. In this case the demand for the food grain will fall, while the need for the fodder grain will grow.In Kedainiai and Panevezys sugar plants the production of sugar has been modernised during the last few years. The technology has been improved so all the sugar made at the “Danisco Sugar” plant in Lithuania meets the requirements of the world and the EU, raised for the white crystal sugar. The quality of the beets grown in Lithuania is high, the qualifications of the local employees is proper and “Danisco Sugar” technologies and experience in international market, enable the factory to gain its place in this competitive market.